Perbandingan Pijat Payudara dan Pijat Oksitosin Terhadap Produksi ASI Ibu Menyusui di PMB Ika Nuraeni Kelurahan Ciburial Pandeglang Banten - Titin Eka Sugiatini; Elis Lisdiani (Jurnal Ners, 2025)
The smooth production and release of breast milk is very important for the health of mother and baby, however many mothers experience difficulty in expressing breast milk. Breast massage and oxytocin massage are two techniques that can help smooth breast milk release. Breast massage focuses on physical stimulation of the breasts, while oxytocin massage stimulates the release of the hormone oxytocin to increase the letdown reflex.Objective: To determine the comparison of breast massage and oxytocin massage on breast milk production in PMB Ika Nuraeni S.Tr Keb, Bdn Kelurahan Ciburial, Cimanggu District, Pandeglang Regency, Banten in 2024.Method: The total respondents in this study were 30 respondents calculated based on data from breastfeeding mothers in the PMB Ika Nuraeni S.Tr Keb area, Bdn Kelurahan Ciburial, Cimanggu District, Pandeglang Regency, Banten, which were divided into two groups, namely 15 respondents in the breast massage group and 15 respondents in the oxytocin massage group taken by purposive sampling using a t-test, namely an independent sample t-test.Results: In the group that underwent breast massage and oxytocin massage on breast milk production, a difference in breast milk production was found, which was mostly found in oxytocin massage with an average of 38.47 ml. before and after breast massage and oxytocin massage, a difference of 19 ml was obtained more oxytocin massage. The results of the independent sample t test obtained a p value = 0.004, which means that there is a difference in breast massage and oxytocin on breast milk production in breastfeeding mothers.Conclusion and Suggestion: to try breast care techniques and oxytocin massage if you have difficulty in producing breast milk. Gentle massage on the breast or back area can help stimulate the release of the hormone oxytocin which is important in facilitating breast milk production